Maxillary Overdentures Supported by Four Splinted Direct Metal Laser Sintering Implants: A 3-Year Prospective Clinical Study - Francesco Mangano; Fabrizia Luongo; Jamil Awad Shibli; Sukumaran Anil; Carlo Mangano (Hindawi Limited, 2014)
Purpose. Nowadays, the advancements in direct metal laser sintering (DMLS) technology allow the fabrication of titanium dental implants. The aim of this study was to evaluate implant survival, complications, and peri-implant marginal bone loss of DMLS implants used to support bar-retained maxillary overdentures. Materials and Methods. Over a 2-year period, 120 implants were placed in the maxilla of 30 patients (18 males, 12 females) to support bar-retained maxillary overdentures (ODs). Each OD was supported by 4 implants splinted by a rigid cobalt-chrome bar. At each annual follow-up session, clinical and radiographic parameters were assessed. The outcome measures were implant failure, biological and prosthetic complications, and peri-implant marginal bone loss (distance between the implant shoulder and the first visible bone-to-implant contact, DIB). Results. The 3-year implant survival rate was 97.4% (implant-based) and 92.9% (patient-based). Three implants failed. The incidence of biological complication was 3.5% (implant-based) and 7.1% (patient-based). The incidence of prosthetic complication was 17.8% (patient-based). No detrimental effects on marginal bone level were evidenced. Conclusions. The use of 4 DMLS titanium implants to support bar-retained maxillary ODs seems to represent a safe and successful procedure. Long-term clinical studies on a larger sample of patients are needed to confirm these results.